Continuous methanol synthesis directly from methane and steam over Cu(II)-exchanged mordenite - Lee, Sae Ha; Kang, Jong Kyu; Park, Eun Duck (Korean Journal of Chemical Engineering, 2018)
The formation of methanol directly from methane and steam was observed over Cu ion-exchanged mordenite. Furthermore, the continuous production of methanol was achieved by co-feeding methane and steam over Cumordenite. The methanol production rate was comparable to that reported in the stepwise process in which activation, methane reaction, and extraction of methanol were carried out separately.
Keywords: Copper; Methane Activation; Methanol; Mordenite; Steam